2014
DOI: 10.1371/journal.pone.0099969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interface Pressure Distribution on Human Sleep Quality

Abstract: High sleep quality promotes efficient performance in the following day. Sleep quality is influenced by environmental factors, such as temperature, light, sound and smell. Here, we investigated whether differences in the interface pressure distribution on healthy individuals during sleep influenced sleep quality. We defined four types of pressure models by differences in the area distribution and the subjective feelings that occurred when participants slept on the mattresses. One type of model was showed “over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Better pressure distribution may have reduced discomfort at sites of compression on the body's surface, reducing the fragmentation of SWS. Chen et al [11] reported that differences in pressure distribution of mattresses affected sleep. In the study, increase in SWS and the decrease in micro-arousals were observed in participants sleeping on pressure intermediately distributed mattress, compared to the ones that were overly-concentrated or overly-even in distribution of pressure [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Better pressure distribution may have reduced discomfort at sites of compression on the body's surface, reducing the fragmentation of SWS. Chen et al [11] reported that differences in pressure distribution of mattresses affected sleep. In the study, increase in SWS and the decrease in micro-arousals were observed in participants sleeping on pressure intermediately distributed mattress, compared to the ones that were overly-concentrated or overly-even in distribution of pressure [11].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [11] reported that differences in pressure distribution of mattresses affected sleep. In the study, increase in SWS and the decrease in micro-arousals were observed in participants sleeping on pressure intermediately distributed mattress, compared to the ones that were overly-concentrated or overly-even in distribution of pressure [11]. In the present study, body pressures were actually lower with the functional mattress for all participants in every posture compared to the control mattress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations